Health Care Disparities Add Insult to Spinal Cord Injury. Issue 6 (December 2021) - Escalon, Miguel X.; Houtrow, Amy; Skelton, Felicia; Verduzco-Gutierrez, Monica
Abstract : The authors describe the disparities and increased risk of traumatic spinal cord injury Black Americans face because of violence. This article should serve as a realization of these inequities and as a call to action to improve the equity of rehabilitation services in this population to improve outcomes.